2022
DOI: 10.3390/ph15121548
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Danshensu Cream Promotes the Healing of Pressure Ulcers in Mice through the Nrf2/HO-1 and NF-κB Pathways

Abstract: On the basis of the mice pressure ulcers (PU) model, the protective effect and potential mechanism of sodium Danshensu (SDSS) cream against PU were investigated. The mice were randomly divided into three groups: the negative control group (cream without 0.5 g SDSS), the SDSS group (cream containing 0.5 g SDSS), and the positive group (0.5 g Hirudoid®). After 7 and 14 days of ointment application, the wound-healing rate of the SDSS and positive groups was significantly higher than that of the control group (p &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The NRF2/HO-1 signaling pathway participates in the regulation of various stress environments by regulating antioxidant and phase 2 detoxifying enzymes, in addition to related proteins [56,57]. Under oxidative stress, NRF2 activates downstream proteins such as NQO1, HO-1, and GCLM, which enhances the coupling reaction and the expression of related antioxidant enzymes (e.g., SOD, GSH-Px, and CAT), thus protecting against oxidative-stress-induced damage [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…The NRF2/HO-1 signaling pathway participates in the regulation of various stress environments by regulating antioxidant and phase 2 detoxifying enzymes, in addition to related proteins [56,57]. Under oxidative stress, NRF2 activates downstream proteins such as NQO1, HO-1, and GCLM, which enhances the coupling reaction and the expression of related antioxidant enzymes (e.g., SOD, GSH-Px, and CAT), thus protecting against oxidative-stress-induced damage [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding isolated compounds, several studies have reported their wound healing capacities. Indeed, wound healing properties have been reported for rosmarinic acid [ 67 , 68 ], salvianolic acid A, and danshensu [ 69 , 70 , 71 , 72 ]. The aglycone apigenin also promotes in vitro and in vivo wound healing [ 73 , 74 , 75 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other naturally derived treatments were also shown to promote chronic wound healing by activating Nrf2 signalling. These treatments include the flavonoids: xanthohumol, procyanidin B2, pterostilbene, curcumin, resveratrol and gallocatechin in addition to other naturally derived treatments: dimethyl fumarate, cordyceptin, bee venom, puffball spores, sodium danshensu and paeoniflorin [ 21 , 40 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ]. There are a few drawbacks that are limiting the use of naturally derived treatments in the clinic.…”
Section: Nrf2 Signalling Pathwaymentioning
confidence: 99%